Influence of voltage deviations on the drive characteristics of working machines with dc motors of independent and parallel excitation at Mc=const - Sinyavsky, O.; Savchenko, V.; Antonyuk, A.; Podobailo, V. (Energy and Automation, 2025)
Voltage deviation in DC motors leads to losses that have an electromagnetic and technological component. Studies on the influence of voltage deviation and asymmetry on the technological and energy characteristics of working machines and mechanisms with an asynchronous electric drive have shown that when they deviate, productivity decreases and specific energy consumption increases. However, there are no studies on the influence of voltage deviation on DC electric drives. The purpose of the study is to establish the influence of voltage deviation in electric drives with DC motors of independent and parallel excitation on the technological and energy characteristics of working machines with a static resistance moment independent of angular velocity. When the voltage deviates, the angular velocity of DC motors of independent and parallel excitation changes, which causes a change in the productivity of the working machine. In DC motors of independent excitation, the dependence of the productivity of the working machine on the voltage change is linear, and in DC motors of parallel excitation, the productivity of the working machine during voltage deviation changes according to a complex algorithm. When the voltage deviates, the constant and variable power losses in the DC electric motor change. It is proposed to conduct an energy assessment of a DC electric drive based on specific electricity consumption. The study of the influence of voltage deviation on the energy characteristics of working machines with a constant moment of static resistances, which are driven by DC motors of independent and parallel excitation, was carried out. It was established that with a decrease in voltage, specific electricity losses increase. Key words: DC motor with independent and parallel excitation, voltage deviation, specific power consumption